Some Reasons for Differences in Charitable Giving Between Countries (Global Journal of Human-Social Science, 2013)
This paper employs cross country regression analysis on a large set of countries to look at a few potential determinants of differences in charitable giving across countries. In addition to present income, it finds that the perceived degree of control over future economic conditions matters for charitable giving. Religiosity and perceptions of corruption also appear to be relevant for charitable donations, with religiously exerting a positive effect and corruption perceptions a negative effect on charity